2016
DOI: 10.4278/ajhp.140326-quan-121
|View full text |Cite
|
Sign up to set email alerts
|

Small Convenience Stores and the Local Food Environment: An Analysis of Resident Shopping Behavior Using Multilevel Modeling

Abstract: Purpose. Local food environments can influence the diet and health of individuals through food availability, proximity to retail stores, pricing, and promotion. This study focused on how small convenience stores, known in New York City as bodegas, influence resident shopping behavior and the food environment.Design. Using a cross-sectional design, 171 bodegas and 2118 shoppers were sampled. Setting. Small convenience stores in New York City. Subjects. Any bodega shopper aged 18þ who purchased food or beverage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
95
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(102 citation statements)
references
References 30 publications
5
95
2
Order By: Relevance
“…Most studies using customer intercept interviews in small food stores have not reported participation rates or information on non-participants (68,15) . Our rate is slightly higher than the 32.9% participation rate reported by Ruff et al (2016) in recent study that used a similar methodology in small, urban food stores (9) . A higher participation rate (53% – 63%) was found by Dannefer et al (2012) (11) , but customer interviews in that study were only conducted in a small subset of eligible stores selected “on the basis of the owners' willingness” to participate, which may have offered a setting particularly amenable to recruitment.…”
Section: Discussioncontrasting
confidence: 72%
“…Most studies using customer intercept interviews in small food stores have not reported participation rates or information on non-participants (68,15) . Our rate is slightly higher than the 32.9% participation rate reported by Ruff et al (2016) in recent study that used a similar methodology in small, urban food stores (9) . A higher participation rate (53% – 63%) was found by Dannefer et al (2012) (11) , but customer interviews in that study were only conducted in a small subset of eligible stores selected “on the basis of the owners' willingness” to participate, which may have offered a setting particularly amenable to recruitment.…”
Section: Discussioncontrasting
confidence: 72%
“…Retail stores, including supermarkets, supercenters, and small stores are in the business of prompting people to purchase foods (6) to make a profit. Typical ways to promote food and beverage products are featured advertisements, product displays, and point-of-purchase availability (1). The food industry pays substantially to place products in stores, especially near the checkout (6).…”
Section: Discussionmentioning
confidence: 99%
“…The food industry pays substantially to place products in stores, especially near the checkout (6). However, the impact of these promotional strategies varies by consumer and store type (1,27). For instance, customers may associate certain store types with certain types of food items, regardless of the marketing features present; for example, at food–gas marts people may expect advertisements for less healthful items and go there to purchase them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations